An information-DNA based method of information dissemination and evolution on Internet - Panpan LI; Zhengxia XIE; Zengkai WANG; Rui JIN (Dianxin kexue)
To solve the problem of how to trace the information content dissemination and evolution process on the Internet, an information DNA-based method of information dissemination and evolution on Internet was proposed.Firstly, semantic extraction of Internet information content was performed based on domain knowledge to form a key feature set of information content.Then, using the key feature set of information content, an information DNA construction method based on locally sensitive hashing was proposed.Finally, the usability and effectiveness of the proposed method were verified by public dataset.The problem of traceability of Internet homologous information dissemination and evolution process was solved by using information DNA as the core identifier, which was of great practical significance for the study of Internet information content dissemination, evolution tracing and the governance and guidance of Internet public opinion events.